PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP KEPUASAN MASYARAKAT : (Studi Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Ambon) - Wattimena, Roy Alan (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2021)
Measurement of the level of community satisfaction must be carried out on an ongoing basis because people's lives will continue to change in terms of their wants, needs and demands as well as consumption patterns in line with changes in the business world environment and technological developments. The purpose of this study was to analyze the effect of service quality on the satisfaction of the people who use the services of the Ambon City Investment and One-Stop Services Office. data were collected from 100 respondents randomly and analyzed using multiple regression analysis. This research has differences from several previous studies which were replicated in the form of analysis techniques and differences in research locations which were culturally, economically and socially different from previous research locations.Based on descriptive analysis, the average score of the Five Dimensions of Service Quality which indicates the level of customer satisfaction with public service performance is as follows: reliability dimension, assurance dimension, responsiveness dimension, direct evidence dimension ( tangibles), and dimensions of empathy (empathy).Based on inferential analysis, (loading factor) which shows the contribution of a dimension to the factor formed in this case is the quality of public service performance at the Ambon City One-Stop Investment and Integrated Service Office, successively from the largest to the smallest is as following: responsiveness dimension, reliability dimension, assurance dimension, tangibles dimension and empathy dimension. Keywords: Service Quality, Community Satisfaction